A humanized orthotopic mouse model for preclinical evaluation of immunotherapy in Ewing sarcoma - Luo, Wen; Hoang, Hai; Liao, Yanling; Pan, Jian; Ayello, Janet; Cairo, Mitchell S. (Frontiers in Immunology, 2023)
The advent of novel cancer immunotherapy approaches is revolutionizing the treatment for cancer. Current small animal models for most cancers are syngeneic or genetically engineered mouse models or xenograft models based on immunodeficient mouse strains. These models have been limited in evaluating immunotherapy regimens due to the lack of functional human immune system. Development of animal models for bone cancer faces another challenge in the accessibility of tumor engraftment sites. Here, we describe a protocol to develop an orthotopic humanized mouse model for a bone and soft tissue sarcoma, Ewing sarcoma, by transplanting fresh human cord blood CD34 + hematopoietic stem cells into young NSG-SGM3 mice combined with subsequent Ewing sarcoma patient derived cell engraftment in the tibia of the humanized mice. We demonstrated early and robust reconstitution of human CD45 + leukocytes including T cells, B cells, natural killer cells and monocytes. Ewing sarcoma xenograft tumors successfully orthotopically engrafted in the humanized mice with minimal invasive procedures. We validated the translational utility of this orthotopic humanized model by evaluating the safety and efficacy of an immunotherapy antibody, magrolimab. Treatment with magrolimab induces CD47 blockade resulting in significantly decreased primary tumor growth, decreased lung metastasis and prolonged animal survival in the established humanized model. Furthermore, the humanized model recapitulated the dose dependent toxicity associated with the CD47 blockade as observed in patients in clinical trials. In conclusion, this orthotopic humanized mouse model of Ewing sarcoma represents an improved platform for evaluating immunotherapy in bone and soft tissue sarcoma, such as Ewing sarcoma. With careful design and optimization, this model is generalizable for other bone malignancies.